En la prueba Wall Drop Punt Kick & Catch, ¿quién gana: la parte interna del pie o el empeine? - Matos, Rui (2024)
WDPK&C test requires the manipulation of a ball with both the upper (releasing and catching) and the lower (kicking) limbs. The present study aimed to: i) identify which (if any) of two different foot parts (inner part or instep) would imply a better performance on WDPK&C; ii) verify if a significant correlation between both foot parts’ test performance could be found, and iii) search for differences between early (10-13 years-old) and middle (14-17 years-old) adolescents on the afore mentioned variables. Thirty-four young male basketball players (14.59 ± 1.93 years-old) participated in this study. Considering the global sample, as well as for the early adolescents’ group alone, using the instep revealed to have greater efficacy than using the inner part of the foot. Besides, very strong (global sample and middle adolescents) and strong (early adolescents) correlations between both foot parts performance were found. However, considering the middle adolescents exclusively, no foot part performance supremacy was found. It seems that the greater efficacy on WDPK&C test using instep disappears when passing from early adolescence to middle adolescence, on male basketball players, probably due to a rise in maturation and years of practice.